1992
DOI: 10.1002/sca.4950140606
|View full text |Cite
|
Sign up to set email alerts
|

Determination of fixed electron‐beam‐induced positive oxide charge

Abstract: Contrary to previous beliefs, electron‐beam‐induced positive charges in insulators persist where created for at least several weeks without discernible movement. Formerly, coating with a thin metal overlay was thought to allow the charge to leak away. Coating with a conductor is shown to shield electric fields from affecting the imaging probe, but to remove no charge from the specimen. A new technique is introduced for the evaluation of the properties of electron‐beam‐induced positive charges in metal‐oxide‐se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In this study, we demonstrate site-specific immobilization of multiple DNA sequences on nanopatterns created by advanced lithographic tools. It is known that surface charging occurs following the electron beam exposure of an insulator. Recently Chi et al . have shown that the positive charge generated at the top surface of a SiO 2 insulating layer by the electron beam exposure can be used to immobilize negatively charged DNA molecules at the nanoscale.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we demonstrate site-specific immobilization of multiple DNA sequences on nanopatterns created by advanced lithographic tools. It is known that surface charging occurs following the electron beam exposure of an insulator. Recently Chi et al . have shown that the positive charge generated at the top surface of a SiO 2 insulating layer by the electron beam exposure can be used to immobilize negatively charged DNA molecules at the nanoscale.…”
Section: Resultsmentioning
confidence: 99%